Assessment of hearing loss in multi-drug resistant tuberculosis (MDR-TB) patients undergoing Aminoglycoside treatment - Nizamuddin, Sheikh; Khan, Farhan Ahmad; Khan, Abdur Rehman; Kamaal, Chand Miyan (International Journal of Research in Medical Sciences, 2017)
Background: Incomplete treatments and treatment failures has led to Multi-drug resistant tuberculosis, which has emerged as a significant problem in treating tuberculosis and thus the second line drugs are used with the concomitant increase in the incidence of adverse effects. Methods: This prospective study was carried out from June 2009 to May 2014 in the department of ENT in collaboration with TB & Chest at Teerthanker Mahaveer Medical College & Research Centre. Out of 104, only 84 patients were included in our study. Patients were divided into three groups: group I (n=27) patients using Amikacin, group II (n=40) patients using kanamycin and group III (n=17) patients using streptomycin. Baseline pre-treatment pure tone audiometry was performed on all the patients and repeated every three months until completion of therapy. Results: Patients included were 15 to 55 years age with higher number of males (65%, n=55) than females (35%, n =29). Only 22.7% (n=19) of patients were found to be suffered from Hearing Loss. At the end of the study (at 12 month), Overall incidence of HFL was 58.0% (n=11) while incidence of Dead ear was 31.5% (n=6) and LFL was 10.5% (n=2). Amikacin was found to be more Ototoxic than Kanamycin and streptomycin. Conclusion: Aminoglycosides in MDR-TB patients may cause irreversible hearing loss involving higher frequencies and can become a hearing handicap as speech frequencies are too implied in more or less of the patients, thus underlining the need for regular audiologic evaluation in patients of MDR-TB during the treatment.